Manajemen Kepala Madrasah dalam Mengembangkan Sumber Daya Manusia di Madrasah Diniyah - Ifan Fahmi; Sutrisno (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2023)
Abstract: This research aims to find out clearly about the management of madrasah heads in developing human resources at Madrasah Diniyah Fathul Ulum Diwek Jombang. The data collection methods used were in-depth interviews, observation and documentation. Data analysis techniques are carried out throughout the data collection process and after all the data has been collected, the data validity test is carried out by testing the credibility of the data. As for the results of this research, it can be concluded that madrasa heads in developing human resources have concepts and strategies as well as supporting and inhibiting factors for these activities. The concept has been implemented as well as the madrasa head's strategy by holding teacher development training and comparative studies to schools or Other madrasas and madrasa heads provide special seminars to teaching staff, while the supporting factors are the emergence of a sense of concern for one another, while the inhibiting factors are discommunication and lack of facilities and infrastructure.